2013
DOI: 10.1017/s0890060413000255
|View full text |Cite
|
Sign up to set email alerts
|

The function analysis diagram: Intended benefits and coexistence with other functional models

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0890060413000255How to cite this article: Marco Aurisicchio, Rob Bracewell and Gareth Armstrong (2013). The function analysis diagram: Intended benets and coexistence with other functional models. AbstractUnderstanding product functions is a key aspect of the work undertaken by engineers involved in complex system design. The support offered to these engineers by existing modeling tools such as the function tree and the function structure is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 35 publications
0
40
0
3
Order By: Relevance
“…We see this encouragement to think beyond prior art as the opposite to design fixation (Jansson and Smith 1991). It has been suggested that FAD needs a better developed syntax in order to be consistent and reliable (Aurisicchio et al 2013). Our use of domain-specific ontologies in FAD?…”
Section: Developing Fad1 As a Graphical Patent Image Annotation Toolmentioning
confidence: 94%
See 1 more Smart Citation
“…We see this encouragement to think beyond prior art as the opposite to design fixation (Jansson and Smith 1991). It has been suggested that FAD needs a better developed syntax in order to be consistent and reliable (Aurisicchio et al 2013). Our use of domain-specific ontologies in FAD?…”
Section: Developing Fad1 As a Graphical Patent Image Annotation Toolmentioning
confidence: 94%
“…Figure 5 shows the cross section detail of a 1952 patented can end design in which a felt Shield (label 21) protects the Raw cutting edge when the Score line (label 15) is broken, and it also serves as a Reclosure element for the can. Figure 6 shows conventional FAD applied to the 1952 patent following the procedure outlined in (Aurisicchio et al 2012). Features of the invention are represented in the boxes where feature names and functional interactions use the phrases stated in the patent and only useful functional interactions are shown in the figure.…”
Section: Representing Functional Geometry Interactionmentioning
confidence: 99%
“…To enhance the ability to abstract and cross-functional communication, the Value Analysis method aims to represent each function simply by the combination of an active verb and a measurable noun. The 'active verb' represents the action performed, and the 'measurable noun' represents the object upon which such action impacts [5,18].…”
Section: Value Engineeringmentioning
confidence: 99%
“…The demand for immediate technological advance and the rise of systems engineering and computer programming, were some of the reasons dictating the development and use of a method allowing us to understand and control complex systems [18]. The active verb -measurable noun taxonomy introduced by Miles [16] was later adapted by the majority of Functional Modelling methods.…”
Section: Functional Modellingmentioning
confidence: 99%
See 1 more Smart Citation